2021
DOI: 10.2174/1573412915666190708162012
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Alogliptin, Linagliptin, Saxagliptin, and Sitagliptin in Bulk Drug and Formulation by UPLC Q-TOF-MS

Abstract: Background: A simple and sensitive Ultra Performance Liquid Chromatography-Mass Spectrometry method was developed and validated to measure the concentrations of Alogliptin (ALO), Linagliptin (LIN), Saxagliptin (SAX), and Sitagliptin (SIT) using Pioglitazone (PIO) as an internal standard. Methods: Chromatographic separation of six gliptins was achieved on a C-18 column (100×2.1 mm, 2.7 µm) using a mobile phase consisting of Formic acid in the water, 0.1%v/v: Acetonitrile in gradient elution. Electrospray io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Few other analytical methods were described for the simultaneous determination of LIG in combination with other antidiabetic agents using HPTLC (El-Kimary et al, 2016;Patel et al, 2020), UPLC/ UV (Ayoub, 2015;Vankalapati et al, 2021), and LC-MS/MS (Al Bratty et al, 2017;Rathod et al, 2020) methods, either in their pharmaceutical dosage form or in human plasma. In addition, other methods were reported for the determination of EMG either alone (Abdel-Ghany et al, 2018;Ayoub, Emam, et al, 2017;Manoel et al, 2021) or in combination with MEF Munde et al, 2020;Riaz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Few other analytical methods were described for the simultaneous determination of LIG in combination with other antidiabetic agents using HPTLC (El-Kimary et al, 2016;Patel et al, 2020), UPLC/ UV (Ayoub, 2015;Vankalapati et al, 2021), and LC-MS/MS (Al Bratty et al, 2017;Rathod et al, 2020) methods, either in their pharmaceutical dosage form or in human plasma. In addition, other methods were reported for the determination of EMG either alone (Abdel-Ghany et al, 2018;Ayoub, Emam, et al, 2017;Manoel et al, 2021) or in combination with MEF Munde et al, 2020;Riaz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that there were few reports published on the simultaneous quantification of dapagliflozin and saxagliptin using UV [8], HPTLC [9], HPLC [10][11][12][13][14][15][16][17][18], and LC-MS [19,20] techniques in bulk drug and pharmaceutical dosage forms. Few methods were reported for analysis of dapagliflozin and saxagliptin separately [21][22][23][24] and in combination with other drugs [25][26][27][28][29]. Literature methods concerted largely on the development and validation of a RP-HPLC methods using different organic phases at different wavelengths and sensitive spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%